PENGARUH MODAL MANUSIA DAN STRUKTUR ASET TERHADAP RISIKO KREDIT DAN KINERJA KEUANGAN PADA BANK KONVENSIONAL DI INDONESIA - Roziq, Ahmad; Sofianti, Septarina Prita Dania; Wasito, Wasito; Sulistiyo, Agung Budi (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to examine the influence of human capital and asset structure on credit risk and financial performance and the influence of credit risk on financial performance of conventional banks in Indonesia. This is an explanatory research with the sample consisted of 25 conventional banks in Indonesia during the period of 2013 to 2017. Data were analyzed using PLS. The results showed that: (a) human capital has no significant influence on credit risk of the conventional banks in Indonesia; (b) human capital has no significant influence on the financial performance of conventional banks in Indonesia, (c) credit risk has significant influence on the financial performance of conventional banks in Indonesia, (d) asset structure has significant influence on the credit risk of conventional banks in Indonesia, and (e) asset structure has no significant influence on the financial performance of conventional banks in Indonesia.